Influence Interpersonal Communication and Leadership on Work Discipline and Their Impact on Teacher Performance of SMK Negeri 8 Palembang - Yuniarti, Yuniarti (Utan Kayu Publishing, 2022)
This study aims to determine the effect of Interpersonal Communication, Leadership and Discipline on the employment of teacher performance at SMK Negeri 8 Palembang. In this study, the population is 60 people as sample tests as samples. Sampling was conducted using the saturated sampling technique sampling is done on the whole of the population. The results of this study are Interpersonal Communication's positive significant effect on employment Discipline Master, Interpersonal Communications positive significant effect on Teacher Performance. Leadership has a positive and significant effect on employment Teacher Discipline, leadership and significant positive effect on teachers' performance. Teachers' work discipline has a positive and significant effect on the performance of teachers of SMK Negeri 8 Palembang, and work discipline is mediating variables Interpersonal Communication relation to the performance and discipline of work is mediating variables Leadership relation to performance. Discipline variable labor has a value r-square of 0.996, meaning that the variable Disciplinary work can be explained by the Interpersonal Communication and Leadership construct 99.6%. Variable Performance r-square value of 0.255 means that the variable performance can be explained by the construct of Interpersonal Communication, Leadership, and the Discipline of the work amounted to 25.5% Based on these conclusions, if the principal of SMK Negeri 8 Palembang intends to increase Interpersonal Communications to improve the performance of teachers, it is necessary to work through increased Discipline Discipline of work is mediating variables Leadership relationship to performance. So based on these conclusions, if the principal of SMK Negeri 8 Palembang. intends to enhance its leadership to increase performance, it is necessary to work through increased Discipline of the three variables used to see the effect on the performance, ie Interpersonal Communication, Leadership, and the Discipline of the work, all of which have a positive effect on performance. But of these three variables, can be prioritized improvement of Leadership. Because of 9 indicators of Leadership., One indicator has a value of loading factor is quite high, namely more than 0.9.